2017
DOI: 10.1177/1049731517745994
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Project P.A.T.H.S. in Mainland China: Findings Based on Student Diaries

Abstract: Objectives: Based on 859 student diaries, the present study evaluated a positive youth development program entitled "Tin Ka Ping (TKP) Positive Adolescent Training through Holistic Social programs (P.A.T.H.S.) " project implemented in mainland China during the 2015-2016 academic year. Method: To understand the perceived effectiveness of the students, the study analyzed quantitative as well as qualitative data derived from the student diaries. Results: The students held very positive views toward the program an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…program has been implemented in junior high schools in Hong Kong. This project was designed based on solid PYD theories and has been systematically evaluated via different assessment tools [50,70]. In Catalano's review of worldwide PYD programs, the "P.A.T.H.S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…program has been implemented in junior high schools in Hong Kong. This project was designed based on solid PYD theories and has been systematically evaluated via different assessment tools [50,70]. In Catalano's review of worldwide PYD programs, the "P.A.T.H.S.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the Tin Ka Ping P.A.T.H.S. Project [50], we invited four junior high schools in mainland China to join a short-term longitudinal study with two waves to study the psychosocial adjustment of Chinese high school students and the related determinants. In the 2016-2017 school year, Grade 7 (N = 1362) and Grade 8 (N = 1648) students participated in the study.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…In view of the very positive evaluation of the “Project P.A.T.H.S.” in Hong Kong, Tin Ka Ping Foundation provided financial support to transplant the program to mainland China (i.e., “Tin Ka Ping P.A.T.H.S. Project”) where the program has displayed very good impacts as well ( Shek, 2019 ; Shek et al, 2019b ; Zhu and Shek, 2020 ). As there are growing mental health problems among Chinese adolescents (e.g., Lo et al, 2018 ; Shek and Siu, 2019 ), PYD programs constitute a promising approach to promote adolescent holistic development utilizing the principles of primary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the other studies in the field (e.g., Shek et al, 2018 , 2019b ), we treated age, gender, and family intactness as covariates. Previous studies showed that demographic variables such as age and gender might have a weak relationship with adolescent well-being ( Proctor et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subjective outcome evaluation findings revealed positive findings [14], the project focused on training in 2014/15 school year. From 2015/16 to 2017/18 school year, the project was implemented in more than 30 schools in China [15]. Client satisfaction and qualitative evaluation findings are very positive (Table 2).…”
Section: Tin Ka Ping Paths Project (2011-2018)mentioning
confidence: 96%